HUBUNGAN ANTARA STRES KERJA DENGAN KELELAHAN KERJA PADA PERAWAT DI RUMAH SAKIT UMUM DAERAH (RSUD) DELI SERDANG LUBUK PAKAM - Hengky Ardian (Jurnal Penelitian Keperawatan Medik, 2019)
Stress is an adaptive response to a situation that is perceived to challenge or threaten a person's health. Work stress in nurses is one of the problems in the management of human resources at the hospital. This study aims to determine the relationship between job stress with job burnout in nurses Regional General Hospital (Hospital) Deli Serdang Lubukpakam. The method used in this study using a type of analytical research with cross sectional design. Gamma test results between job stress with job burnout in nurses obtained significant values (p) obtained was 0,016. To view the results of significant statistical calculations used the limit of significance α = 0.05. Based on the above values indicate significant p value <0.05 which means that the hypothesis there is a relationship between job stress and fatigue in nurses working at the General Hospital (Hospital) Deli Serdang Lubukpakam accepted. There was a significant relationship between work stress fatigue. The need for provision of extension or improvement of knowledge about the factors that can lead to work stress, work fatigue and how to treat the condition.